A Case of Primary Hyperparathyroidism due to a Intrathyroid Parathyroid Adenoma with Chronic Kidney Disease and Wegner’s Granulomatosis (Bangladesh Journal of Otorhinolaryngology, 2025)
Primary hyperparathyroidism due to intrathyroid parathyroid adenoma is extremely rare. This case is important as this patient was known case of CKD so it was difficult to differentiate this case from secondary and tertiary hyperparathyroidism. It was also challenging for surgeon to take appropriate peroperative decision to perform hemithyroidectomy as there was no radiological evidence of intrathyroid parathyroid adenoma and also challenging when all probable sites and ectopic sites were meticulously searched and no parathyroid adenoma was formed.Bangladesh J Otorhinolaryngology 2024; 30 (2): 84-87